2022
DOI: 10.3390/ijms23052885
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Hypoxia Affects Foetal Cardiovascular Regulatory Mechanisms in a Sex- and Circadian-Dependent Manner: A Review

Abstract: Prenatal hypoxia during the prenatal period can interfere with the developmental trajectory and lead to developing hypertension in adulthood. Prenatal hypoxia is often associated with intrauterine growth restriction that interferes with metabolism and can lead to multilevel changes. Therefore, we analysed the effects of prenatal hypoxia predominantly not associated with intrauterine growth restriction using publications up to September 2021. We focused on: (1) The response of cardiovascular regulatory mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 227 publications
(323 reference statements)
1
14
0
2
Order By: Relevance
“…Angiolin is able, together with vitamin C, to form L-carnitine and normalize the work of mitochondria [21]. In our work, it was found that angiolin normalized the amplitudes of the ventricular R wave and the amplitude of the repolarization T wave under conditions of myocardial ischemia, which is associated with an improvement in the energy supply of the myocardium and a more rational use of macroergs to ensure the contractile function of the heart [12]. Angiolin increases the expression of HSP 70 , which "prolongs" the action of HIF-1a, and also independently maintains the expression of NAD-MDH-mx, thereby maintaining the activity of the compensatory mechanism of ATP productionthe malate-aspartate shuttle mechanism for a long time.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Angiolin is able, together with vitamin C, to form L-carnitine and normalize the work of mitochondria [21]. In our work, it was found that angiolin normalized the amplitudes of the ventricular R wave and the amplitude of the repolarization T wave under conditions of myocardial ischemia, which is associated with an improvement in the energy supply of the myocardium and a more rational use of macroergs to ensure the contractile function of the heart [12]. Angiolin increases the expression of HSP 70 , which "prolongs" the action of HIF-1a, and also independently maintains the expression of NAD-MDH-mx, thereby maintaining the activity of the compensatory mechanism of ATP productionthe malate-aspartate shuttle mechanism for a long time.…”
Section: Discussionmentioning
confidence: 71%
“…Our previous studies have obtained data indicating the role of the NO system in the formation of post hypoxic cardiomyopathy. So, in children who underwent intrauterine hypoxia, a deficiency of stable NO metabolites was found in blood against the background of eNOS inhibition [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, animal models of prenatal hypoxia have been widely used to understand the molecular mechanisms of adverse outcomes in offspring. Prenatal hypoxia affects fetal growth and elicits many disturbances after birth including the development of the central nervous system and cardiovascular regulatory system ( Peyronnet et al, 2000 ; Wang et al, 2021 ; Sutovska et al, 2022 ). Decreased oxygen supply and peripheral blood flow by gestational IH to the fetal organs such as the heart and brain have critical impacts on physiological functions of these organs ( Baschat et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…The circadian system develops “in utero” through exposure to maternal cues [ 20 , 21 ]. The importance of maternal–fetal communication is well known for other environmental factors such as nutrition, stress, and hypoxia, resulting in the development of diseases in adulthood [ 22 ]. The risk of maternal exposure to constant light during the second part of pregnancy has recently been underlined by the possibility that suppressed maternal melatonin can modify the epigenome of the fetal liver [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%